2013
DOI: 10.1007/s11250-013-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

Production and economic performance of F1-crossbred dairy cattle fed non-conventional protein supplements in Zimbabwe

Abstract: The effects of supplementing crossbred cows with non-conventional protein sources on dry matter intake, milk yield parameters and economic returns were investigated. Twenty-five lactating F1 Holstein-Mashona crossbreds averaging 115 ± 24 days in milk were used. Five treatments, total mixed ration (TMR), urea-treated maize stover, untreated maize stover, Macroptilium atropurpureum (Siratro) hay and veld hay, were randomly assigned to cows and replicated five times in a completely randomised design. Nutrient com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…Some also reported a long calving interval due to a low bull:cow ratio and poor nutrition. In a study by Nqeno Gusha et al (2014) reported heifer mating ages of between 18 and 27 months in Zimbabwe. Contrary to these findings, Tada et al (2013) found that most heifers in the Eastern Cape had a calf before reaching four years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Some also reported a long calving interval due to a low bull:cow ratio and poor nutrition. In a study by Nqeno Gusha et al (2014) reported heifer mating ages of between 18 and 27 months in Zimbabwe. Contrary to these findings, Tada et al (2013) found that most heifers in the Eastern Cape had a calf before reaching four years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Acacia angusitissima, Leuceana leucocephala, and Calliandra calothyrsus are browse legumes, while Macroptilium atropuprium is a forage legume that have been extensively promoted for use in small scale dairying and communal livestock production (Masama et al, 1997;Ngongoni et al, 2006;Baloyi et al, 2009;Chakoma, 2012;Zvinorova et al, 2013). These legume forages have high crude protein and minerals especially calcium and phosphorus (Gusha et al, 2014). However, these forages have a significant amount of anti-nutritional factors which sometimes limit their utilisation (Masama et al, 1997;Baloyi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates a quality, not only of proteins, in providing tissue growth, but also a higher digestion ability of their carbohydrates, also indicating the capacity of reducing the amount of concentrated proteins (soybean meal) and mineral sources in feed with the substitution (Table 1). The legume forages have high CP and minerals especially Ca and P (Gusha et al, 2014). Gusha et al (2013) reported that legumes have demonstrated in in vitro and in vivo digestibility studies that they can be used as protein supplements.…”
Section: Discussionmentioning
confidence: 99%